The adsorption of Cr(VI) on sulphuric acid-treated wheat bran - Özer, A; Özer, D (Taylor & Francis Ltd, 2004)
Wheat bran, a by-product of wheat milling industries, was converted into a cheap and efficient material by treating with sulphuric acid and used for the adsorption of Cr(VI) from aqueous solution. Effects of various parameters such as initial pH of solution, contact time, initial Cr(VI) concentration and temperature were studied. The sulphuric acid-treated wheat bran (STWB) gave the highest adsorption efficiency at pH 1.5. The equilibrium data were fitted better to Langmuir isotherm model compared to Freundlich model at all the temperatures studied. The adsorption capacity increased from 91 to 133 mg g(-1) with an increase in temperature from 20 degreesC to 50 degrees. The adsorption process was found to be endothermic and Langmuir isotherm data were evaluated to determine the thermodynamic parameters for the process. Thermodynamic parameters showed that the process was feasible. The results indicated that the chromium removal process by STWB followed first-order rate expression and adsorption rate constants increased with increasing temperature.
Keywords: wheat bran; sulphuric acid-treated; adsorption; Cr(VI) ions